Infrastructure Rollout and Fibre Provision: The case of NGN in the Netherlands - M. W. W. Sahebali; Bert M. Sadowski; O. Nomaler; R. Brennenraedts (International Telecommunications Society (ITS), 2019)
Within the growing literature on next generation network (NGN), much research has focused on infrastructure competition and spatial effects driving investment incentives in NGN provision. However, less attention has been paid to the dynamic factors explaining NGN rollout. The purpose of this paper is to examine the geographical effects of NGN rollout by utilizing basic data mining techniques in conjunction with exploratory spatial data analysis. In explaining NGN rollout, the paper derives a dynamic geographical model on NGN provision and examines it empirically by focusing on the spatial and temporal effects driving NGN development in the Netherlands. The paper confirms previous research on market uncertainty and the techno-economics of NGN development, but shows, in addition, that more specific factors related to local effects and demand uncertainty are vital in explaining NGN rollout.
Keywords: 330